2011
DOI: 10.1179/174329211x12968219310837
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of aminoguanidine against cyclophosphamide-induced oxidative stress and renal damage in rats

Abstract: The results of the present study reveal that AG can prevent CP-induced renal damage by inhibiting oxidative stress. Thus, AG may be useful for prevention of the nephrotoxicity of CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 44 publications
5
14
0
Order By: Relevance
“…For evaluating the antioxidant activity in renal tissue, we measured the renal GSH level, SOD, GPx and CAT activity. Earlier studies have demonstrated that CPinduced nephrotoxicity is associated with depletion of renal antioxidant enzymes such as CAT, SOD, GPx and GSH [5,49]. Our results are in line with the previous studies indicating that a decrease in renal antioxidant enzymes is apparent in treatment with CP.…”
Section: Discussionsupporting
confidence: 93%
“…For evaluating the antioxidant activity in renal tissue, we measured the renal GSH level, SOD, GPx and CAT activity. Earlier studies have demonstrated that CPinduced nephrotoxicity is associated with depletion of renal antioxidant enzymes such as CAT, SOD, GPx and GSH [5,49]. Our results are in line with the previous studies indicating that a decrease in renal antioxidant enzymes is apparent in treatment with CP.…”
Section: Discussionsupporting
confidence: 93%
“…The OS induced by CP in testicular tissue of treated rats in this study was agreed with that previously demonstrated by Abraham and Rabi [22] and Nitharwal et al [23] who concluded that exposure of rats to CP can disrupt the reduction-oxidation (redox) balance in the tissues leading to oxidative stress. Our results are comparable with Ilbey et al [24] who reported that treatment with the anticancer CP resulted in elevated levels of MDA due to the excessive generation of free radicals and reduced levels of GSH, CAT and SOD activities in testis.…”
Section: Discussionsupporting
confidence: 92%
“…Aminoguanidine can primarily scavenge reactive dicarbonyl precursors to AGEs and inhibit the formation of AGEs . It may also inhibit lipid peroxidation and protein oxidation, and protect the activities of antioxidant enzymes including GPx, catalase and GSTase and also MPO, thus preventing inflammation damage . Besides, aminoguanidine also improves neutrophil migration into diabetic wound.…”
Section: Introductionmentioning
confidence: 99%